Coastal mixing in multiple-mouth deltas: A case study in the Po delta, Italy. (15th October 2019) - Bellafiore, Debora; Ferrarin, Christian; Braga, Federica; Zaggia, Luca; Maicu, Francesco; Lorenzetti, Giuliano; Manfè, Giorgia; Brando, Vittorio; De Pascalis, Francesca
Abstract: Satellite imagery provides evidence of complex mixing dynamics in the coastal zone in front of multiple mouth deltas. One peculiar feature, identified in front of the Po Delta (Italy), consists in warmer water bulges present in some periods in the coastal zone between the river mouths. Such features are evident during both high and low river discharge. Through an integrated approach based on the analysis of satellite imagery, in situ field data and a high-resolution oceanographic model, representing the whole river-delta-sea system, we investigated the relative contribution of the different forcing in controlling coastal mixing of riverine waters. The results evidence that the occurrence of these warmer saltier water bulges is due to upwelling induced by the combined action of tides and wind regimes aligned along coastline. Winds from the land and along the coast drive the upwelling through the well-known mechanism described by Ekman. The presence of river discharge enhance the water column stratification, creating the conditions in which tidal action follows the tidal straining theory. Both processes are identified in modelling results. The occurrence of these localized coastal waters with peculiar thermohaline characteristics, detectable on satellite imagery of the area, can be relevant in the definition of the freshwater areas of influence and the mechanisms of riverine water mixing in the near coastal zone. This can shed some light, eventually, on characterizing the sediment dynamics, as well as the thermohaline properties of waters in the area, and also to identify eventual impacts on the local ecosystems and fishery.